Research on investment and financing risk problems and countermeasures of PPP construction projects - Shang, Xingyu (Transactions on Economics, Business and Management Research, 2024)
This study analyzes financing costs, capital liquidity, policy changes and contract execution risks in PPP project investment and financing, and puts forward strategies such as optimizing financing platforms, reducing costs, strengthening regulations, regulatory coordination and improving prevention capabilities. By exploring the causes and effects of risks, combined with domestic and foreign cases to verify the effectiveness of the strategy. This study enriches the theory of PPP risk management, provides guidance for the practical operation of the project, and promotes the healthy development of the PPP project.